HUBUNGAN ANTARA KECENDERUNGAN NARSISME DENGAN MINAT MEMBELI KOSMETIK MEREK ASING PADA PRIA METROSEKSUAL - Apsari, Fitri (TALENTA, 2012)
For metrosexual men, an attractive physical appearance  is one of the potential benefits  for  interacting  with other people.  Attractive appearance  which leads to narcissism  is supported by the cosmetic appearance of  the  foreign and local brands  for men  on the market.  The hypothesis  in  the study  that  there is a correlation  between narcissism   tendencies with  interest in buyng  foreign  brand  cosmetics  of metrosexual men. Subjects are 40 people who met at the outlets of foreign  cosmetic brand with the population study as a  sample  collection  technique. Then researcher obtained  data analysis r <0.348, p = 0.014 (p <0.05). The effective contribution of 14.7%, which there are  85.3%  other factors  that  influence the  propensity  of narcissism  beyond  cosmetics variable interest in  buying  foreign brands,  such as  psychological,  biological,  and sociological. There is a positive relationship between narcissism tendencies with interest in buying foreign brand cosmetics of metrosexual men.